Almost periodic solutions to systems of parabolic equations. (1994) - Nee, Janpou
Abstract : In this paper we show that the second-order differential solution is 𝕃 2 -almost periodic, provided it is 𝕃 2 -bounded, and the growth of the components of a non-linear function of a system of parabolic equation is bounded by any pair of con-secutive eigenvalues of the associated Dirichlet boundary value problems.